Antibiotic self-medication in Otuke District, Northern Uganda: Prevalence and associated factors. - Denis Diko Adoko; Rebecca Nakaziba (PLoS ONE)
Antibiotic self-medication is a growing public health concern, particularly in low- and middle-income countries where access to healthcare is limited. The practice contributes to antimicrobial resistance which increases health care costs, morbidity, and mortality in the population. This study aimed to investigate the prevalence of antibiotic self-medication and its associated factors in the Otuke District, Northern Uganda. A community-based cross-sectional study was conducted in Otuke. Data was collected among adults aged 18 years and above using semi-structured questionnaire. Collected data was coded and double-entered into SPSS Software version 26 and exported to STATA 14 for analysis of frequencies and percentages. Modified Poisson regression was used to run analysis of the association at a P-value of 0.05. Out of the 385 participants, 261 (67.79%) reported having self-medicated with antibiotics in the past six months. The most commonly self-medicated antibiotics were amoxicillin 134 (51.3%), ampiclox 87 (33.3%) and metronidazole 57 (21.9%). Participants with previous successful treatment were 2.33 times more likely to self-medicate (PR = 2.33, 95% CI: 1.89-2.87, P < 0.001) while poor staff attitude increased the likelihood by 1.53 times (PR = 1.53, 95% CI: 1.38-1.71, P < 0.001). Knowledge about antibiotics was negatively associated with ASM in that those who had knowledge on antibiotics were 25% less likely to self-medicate with antibiotics (PR = 0.75, 95% CI: 0.65-0.86, P < 0.001). The practice of antibiotic self-medication was highly prevalent in Otuke district due to previous successful treatments and poor health care systems. The commonly self-medicated antibiotics were amoxicillin, ampiclox and metronidazole. We recommend public health interventions such as community education on antimicrobial resistance regulation of antibiotic use in the country.